Chemocatalytic Production of Lactates from Biomass-Derived Sugars - Heng Zhang; Yulin Hu; Liying Qi; Jian He; Hu Li; Song Yang (International Journal of Chemical Engineering)
In recent decades, a great deal of attention has been paid to the exploration of alternative and sustainable resources to produce biofuels and valuable chemicals, with aims of reducing the reliance on depleting confined fossil resources and alleviating serious economic and environmental issues. In line with this, lignocellulosic biomass-derived lactic acid (LA, 2-hydroxypropanoic acid), to be identified as an important biomass-derived commodity chemical, has found wide applications in food, pharmaceuticals, and cosmetics. In spite of the current fermentation of saccharides to produce lactic acid, sustainability issues such as environmental impact and high cost derived from the relative separation and purification process will be growing with the increasing demands of necessary orders. Alternatively, chemocatalytic approaches to manufacture LA from biomass (i.e., inedible cellulose) have attracted extensive attention, which may give rise to higher productivity and lower costs related to product work-up. This work presents a review of the state-of-the-art for the production of LA using homogeneous, heterogeneous acid, and base catalysts, from sugars and real biomass like rice straw, respectively. Furthermore, the corresponding bio-based esters lactate which could serve as green solvents, produced from biomass with chemocatalysis, is also discussed. Advantages of heterogeneous catalytic reaction systems are emphasized. Guidance is suggested to improve the catalytic performance of heterogeneous catalysts for the production of LA.